STRATEGI CERDAS DI PASAR PROPERTI INDONESIA: PENGHINDARAN PAJAK, KEUNTUNGAN, DAN PERSEDIAAN DI BEI (2018-2022) - Astuti, Wati Aris; Nafis, Silmi Nur Fathiyyah (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
Tax evasion is common in various sectors, including the property industry in Indonesia. This practice can be carried out through manipulation of financial reports, exploiting legal loopholes, or placing investments in areas with lower taxes. This research focuses on the impact of profitability and inventory intensity on tax avoidance in the property and real estate sector. The sample was selected from property and real estate companies listed on the Indonesia Stock Exchange, taking into account the criteria of financial data availability, reporting consistency and adequate industry representation. The research results show that profitability and inventory intensity have a significant influence on tax avoidance in this sector. These findings provide important insights for financial practitioners and regulators in developing more effective and fair tax policies. With a better understanding of the factors that influence tax avoidance, regulators can design more careful policies to prevent practices that harm state tax revenues and create equality in the tax system.